Less (Winner of the Pulitzer Prize): A Novel - Andrew Sean Greer (Amazon Digital Services LLC, 2017)
Who says you can't run away from your problems? You are a failed novelist about to turn fifty. A wedding invitation arrives in the mail: your boyfriend of the past nine years is engaged to someone else. You can't say yes--it would be too awkward--and you can't say no--it would look like defeat. On your desk are a series of invitations to half-baked literary events around the world.